Helicobacter pylori avoids the critical activation of NLRP3 inflammasome-mediated production of oncogenic mature il-1β in human immune cells - Suneesh Kumar, Pachathundikandi; Blaser, Nicole; Bruns, Heiko; Backert, Steffen (Cancers, 2020)
Helicobacter pylori persistently colonizes the human stomach, and is associated with inflammation-induced gastric cancer. Bacterial crosstalk with the host immune system produces various inflammatory mediators and subsequent reactions in the host, but not bacterial clearance. Interleukin-1β (IL-1β) is implicated in gastric cancer development and certain gene polymorphisms play a role in this scenario. Mature IL-1β production depends on inflammasome activation, and the NLRP3 inflammasome is a major driver in H. pylori-infected mice, while recent studies demonstrated the down-regulation of NLRP3 expression in human immune cells, indicating a differential NLRP3 regulation in human vs. mice. In addition to the formation of mature IL-1β or IL-18, inflammasome activation induces pyroptotic death in cells. We demonstrate that H. pylori infection indeed upregulated the expression of pro-IL-1β in human immune cells, but secreted only very low amounts of mature IL-1β. However, application of exogenous control activators such as Nigericin or ATP to infected cells readily induced NLRP3 inflammasome formation and secretion of high amounts of mature IL-1β. This suggests that chronic H. pylori infection in humans manipulates inflammasome activation and pyroptosis for bacterial persistence. This inflammasome deregulation during H. pylori infection, however, is prone to external stimulation by microbial, environmental or host molecules of inflammasome activators for the production of high amounts of mature IL-1β and signaling-mediated gastric tumorigenesis in humans.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Helicobacter pylori; Inflammasome; Interleukin-1β; NLRP3